2005
DOI: 10.1002/anie.200462837
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bending Excitation on the Reaction of Chlorine Atoms with Methane

Abstract: Many chemical reactions are accelerated by heating the reagents. This effect is caused by more energy being partitioned into the reagents electronic, translational, vibrational, and rotational degrees of freedom that ultimately becomes available for overcoming the reaction barrier. Which degrees of freedom are most effective at driving chemical reactions? For endoergic reactions involving an atom and a diatom, Polanyi [1] showed that vibrational excitation of the reagent diatom is the most effective means of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 26 publications
(41 reference statements)
4
33
0
Order By: Relevance
“…In an early dynamical study, Flynn and co-workers employed infra-red absorption spectroscopy of the DCl products of reaction of Cl atoms with d 12 -cyclohexane, 3 but the subsequent combination of resonance enhanced multi-photon ionization (REMPI) or vacuum ultraviolet (VUV) ionization with velocity resolution of reaction products has proved most informative. The velocity information was initially derived from analysis of time-of-flight (TOF) profiles obtained in a TOF mass spectrometer, [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] but velocity map imaging (VMI) 19,20 has since become the method of choice. [21][22][23][24][25][26][27][28][29][30][31][32] The experimental measurements and dynamical calculations for H-atom abstraction reactions involving simple alkanes illustrate a wealth of dynamical behaviour.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an early dynamical study, Flynn and co-workers employed infra-red absorption spectroscopy of the DCl products of reaction of Cl atoms with d 12 -cyclohexane, 3 but the subsequent combination of resonance enhanced multi-photon ionization (REMPI) or vacuum ultraviolet (VUV) ionization with velocity resolution of reaction products has proved most informative. The velocity information was initially derived from analysis of time-of-flight (TOF) profiles obtained in a TOF mass spectrometer, [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] but velocity map imaging (VMI) 19,20 has since become the method of choice. [21][22][23][24][25][26][27][28][29][30][31][32] The experimental measurements and dynamical calculations for H-atom abstraction reactions involving simple alkanes illustrate a wealth of dynamical behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25][26][27][28][29][30][31][32] The experimental measurements and dynamical calculations for H-atom abstraction reactions involving simple alkanes illustrate a wealth of dynamical behaviour. For example, the shape of the transition state, with near linear Cl-H-C moiety, is reflected in the low rotational excitation of HCl products; scattering angles are largely determined by impact parameter and their distributions can vary with product rotational and vibrational quantum states; 1 and the reactions of Cl atoms with methane and partially deuterated isotopologues exhibit reagent vibrational mode specificity, [4][5][6][7][9][10][11][12]14,15,[33][34][35][36][37][38][39][40] electronically non-adiabatic pathways, 29,31,41,42 and evidence for scattering resonances. 43 Reactions of functionalized organic molecules (RH = alcohols, 24,44,45 amines, 46 alkyl halides 23,47 and linear and cyclic ethers 24,44,…”
Section: Introductionmentioning
confidence: 99%
“…If vibrational excitation of the methyl radicals is to be useful in promoting nonadiabatic reactivity and thus production of Cl * , the vibrational motion ͑which is mainly of the CH 3 umbrella bending mode͒ must be retained along the reaction coordinate, at least as far as the TS region. Prior work has clearly shown, however, that a vibrationally adiabatic picture of the reverse Cl+ CH 4 reaction does not hold for bending vibrations, 19 and we expect that the initial bending mode excitation of CH 3 is quenched in the entrance channel of the PES for its reaction with HCl. The symmetric stretch excitation of CH 3 might, in contrast, be preserved along the reaction pathway but it occurs for only 12% of the fast CH 3 radicals 40 and cannot explain the observed Cl * branching of 15%, as fast and slow CH 3 radicals are produced in a 1: 2.1 ratio.…”
Section: A Scattering Dynamicsmentioning
confidence: 67%
“…The reverse reaction of Cl atoms with CH 4 ͑and isotopologs resulting from partial or complete deuteration͒ is well established as a benchmark polyatomic reactive system for studying scattering and vibrational mode and bond specific dynamics. [15][16][17][18][19][20][21][22][23][24] Reaction of Cl * with CH 4 adiabatically correlates with an electronically excited state of the CH 3 radical, and nonadiabatic formation of the energetically accessible CH 3 ͑X 2 A 2 Љ͒ + HCl products is not observed for collisions with energies just above the energetic barrier 25,26 but does occur at much higher collision energies. 27 In studies of the kinetics of collisional processes between Cl * atoms and small hydrocarbons, Matsumi et al 28 demonstrated that the rate of SO quenching of Cl * to grounda͒ Present address: Solar-Terrestrial Environment Laboratory, Nagoya University, Nagoya 464-8601, Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the measured branching ratios (the red bars) showed significant variance with that from the ground-state reaction (either the green or blue bars). In particular, the adiabatically correlated (0, 1 1 ) s pair accounts for only 30% of total reactivity of this isotope channel (a value identical to the other isotope channel may be fortuitous), in significant deviation from the adiabatic expectation or the spectator paradigm (34,35) that the initial excitation of the unreactive C-H bond survives as the (0, 1 1 ) s product pair. Therefore, the initial C-H excitation is counterintuitively not a mere spectator when a D atom is abstracted.…”
Section: Visualizing the Cooperative Atomic Motions While A Chemical mentioning
confidence: 99%